Strategi Pengembangan Wilayah melalui Industrialisasi Berbasis Sektor Unggulan - Shinta Putri Marvina; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Regional development strategies are one of the important steps to improve the economy and distribution of development in various regions. An industry approach that focuses on leading sectors has proven to be an efficient way to maximize the local potential found in each region. This research aims to discuss regional development strategies with emphasis on the use of leading sectors as the main driver of industrialization. This study uses a qualitative approach with the literature review method to explore various studies, reports, and related secondary data. It is known that selecting the appropriate leading sectors, supported by flexible policies and cooperation between the government, industry players, and the community, can increase economic value, create jobs, and strengthen regional competitiveness in a sustainable manner. With a focused and local potential-based approach, industrialization not only accelerates economic growth, but also strengthens the region's economic structure for the long term.